Fighting against the odds - Halvor Mehlum; Karl Moene (University of Oslo, Department of Economics, 2005)
The fight for power is not only over immediate rents, but also over advantageous positions in future power struggles. When incumbency yields an extra fighting edge, current struggles involve high stakes as a victory today may guarantee the victory also tomorrow. Such an incumbency edge may stem from the control of the army, the police and other instruments reserved for the government. The conclusions drawn from static conflict models are turned on their head when the fight is also over the incumbency edge. A sharper incumbency edge increases the implicit prizes of winning. The fighting intensity may therefore rise when the strength of each side becomes more unequal. Unbalanced fights can last long and become particularly severe. This is in contrast to the standard result that equal strengths give the most intense fighting.
Keywords: C70; D23; D74; 330; Violent conflicts; Rent-seeking games; contests; Konflikt; Spieltheorie